Populernya Bahasa Ngapak Banyumasan di Kalangan Konten Kreator Pada Akun Tiktok @raflychaniag0 dan @Desy Genoveva - Syahputra, Dzaki Gentur; Khasanah, Zumrotul (IAINU Kebumen, 2024)
The Ngapak Banyumasa language culture is a form of identity for the Banyumas people which covers the western part of Central Java, consisting of Banjarnegara, Purbalingga, Banyumas and Cilacap. This discovery is based on content creators from the TikTok platform named @raflychaniag0 and @Desy Genoveva, both accounts create TikTok content using the Ngapak language. The aims of this research are (1) to find out how popular the Ngapak language is on TikTok, (2) to find out the differences between the two accounts in creating content in the Ngapak language, (3) to find out how TikTok video viewers respond to the creator's content. use the Ngapak language as their content material. The results of this research show that (1) TikTok content that uses the Ngapak language is a creative idea and is able to attract many viewers because the content contains elements of humor and extensive new information, from here the Banyumasan Ngapak language can be known by outsiders from the people of Banyumas, (2) The difference between these two accounts is in the way they convey the message, with the @raflychaniag0 account, the characteristic is humor or jokes which in the Ngapak language are pronounced firmly, openly and spontaneous, while with the @Desy Genoveva account, the content is more interactive with the audience by inviting other TikTok users to share Ngapak vocabulary in their respective areas. (3) The response in the comments column shows that the TikTok audience for both content These creators felt entertained, they became more aware of the Ngapak language vocabulary and some of them followed suit using the language styles used by content creators.